Hypoxia‐Induced FUS–circTBC1D14 Stress Granules Promote Autophagy in TNBC. Issue 10 (19th February 2023) - Liu, Ying; Liu, Yiwei; He, Yinqiao; Zhang, Ning; Zhang, Siyue; Li, Yaming; Wang, Xiaolong; Liang, Yiran; Chen, Xi; Zhao, Weijing; Chen, Bing; Wang, Lijuan; et al.
Abstract: Triple‐negative breast cancer (TNBC) is a highly aggressive subtype of breast cancer that is suggested to be associated with hypoxia. This study is the first to identify a novel circular RNA (circRNA), circTBC1D14, whose expression is significantly upregulated in TNBC. The authors confirm that high circTBC1D14 expression is associated with a poor prognosis in patients with breast cancer. circTBC1D14‐associated mass spectrometry and RNA‐binding protein‐related bioinformatics strategies indicate that FUS can interact with circTBC1D14, which can bind to the downstream flanking sequence of circTBC1D14 to induce cyclization. FUS is an essential biomarker associated with stress granules (SGs), and the authors find that hypoxic conditions can induce FUS–circTBC1D14‐associated SG formation in the cytoplasm after modification by protein PRMT1. Subsequently, circTBC1D14 increases the stability of PRMT1 by inhibiting its K48‐regulated polyubiquitination, leading to the upregulation of PRMT1 expression. In addition, FUS–circTBC1D14 SGs can initiate a cascade of SG‐linked proteins to recognize and control the elimination of SGs by recruiting LAMP1 and enhancing lysosome‐associated autophagy flux, thus contributing to the maintenance of cellular homeostasis and promoting tumor progression in TNBC. Overall, these findings reveal that circTBC1D14 is a potential prognostic indicator that can serve as a therapeutic target for TNBC treatment. Abstract : FUS‐circTBC1D14‐associated stress granules (SGs) are transferred to the cytoplasm after being modified by PRMT1 and circTBC1D14 increases the stability of PRMT1 by inhibiting its K48‐regulated polyubiquitination. Then FUS‐circTBC1D14 can initiate a cascade of SGs‐linked proteins to control the elimination of SGs by recruiting LAMP1. The findings reveal that circTBC1D14 can serve as a therapeutic target for TNBC treatment.